Exploring The Element Of Allegory And Metaphysical Conceit In The Works Of John Donne’s A Valediction Forbidding Mourning & John Dryden’s Annus Mirrabilis: A Comparative Analysis - Normazla Ahmad Mahir; Zarina Ashikin Zakaria; Mohd Muzhafar Idrus; Norhana Abdullah (USIM Press, 2024)
Vol. 1 No. 1 (2022)